Subclinical hypothyroidism and risk to carotid atherosclerosis - Valentina, Velkoska Nakova; Boshevski Marijan; Chedo, Dimitrovski; Krstevska, Brankica (FapUNIFESP (SciELO), 2011)
OBJECTIVE: The aim of this study was to assess whether subclinical hypothyroidism (SCH) is associated with carotid atherosclerosis, as well as dyslipidemia, and arterial hypertension. SUBJECTS AND METHODS: The study included 69 consecutive patients with newly diagnosed SCH, and 30 matched healthy controls. Body mass index (BMI), TSH, fT4, antibodies to thyroid peroxidase (TPOabs), lipids, blood pressure, mean and maximum carotid intima-media thickness (CIMT) were determined in all participants. RESULTS: Mean values of CIMT, triglycerides, and total cholesterol/HDL-C ratio were significantly different in SCH patients versus matched controls. Linear multiple regression analysis demonstrated that TSH, diastolic blood pressure and triglycerides were independent predictors of mean CIMT, fT4 for maximum CIMT; and that TSH, fT4, age, and total cholesterol/HDL-C ratio were independent predictors of the presence of carotid plaques. CONCLUSION: Our data revealed that SCH is associated with increase in CIMT and presence of carotid plaques, independent of classical risk factors for atherosclerosis.
Keywords: subclinical hypothyroidism; atherosclerosis; dyslipidemia; arterial hypertension; carotid intima-media thickness